Permeability within vocational training with respect to the chemical industry : a pilot project promoted in the context of the European Union Leonardo Da Vinci project for vocational education and training - (:unkn) unknown (My University, 2008)
"The aim of the European Qualifications Framework (EQF) is to promote transparency and mutual trust between different players in the fields of education, vocational education and training, and in further education in Europe. This project 'EQF Chemistry - Permeability within vocational training with respect to the chemical industry' gives concrete answers to the questions of: the permeablity in vocational training and education between different competence levels of non-academic qualifications and the permeability at the interface between non-academic and academic training and edcuation in the production and laboratory areas of the chemical-industry." (Excerpt, BIBB-Doku)

"Ziel des Europäischen Qualifikationsrahmens (EQF) ist u.a. Transparenz und gegenseitiges Vertrauen zwischen den verschiedenen Akteuren in den Bereichen Bildung, Berufsbildung und Weiterbildung in Europa zu fördern. Mit dem Projekt 'EQF Chemie - Durchlässigkeit in der beruflichen Bildung am Beispiel der chemischen Industrie' (gefördert im Rahmen des Programms Leonardo) werden konkrete Antworten auf die Fragen: der Durchlässigkeit in der beruflichen Bildung über verschiedene Kompetenzstufen nichtakademischer Aus- und Weiterbildung sowie der Durchlässigkeit an der Schnittstelle akademische - nichtakademische Aus- und Weiterbildung in den Produktions- und Laborbereichen der chemischen Industrie gegeben." (Textauszug, BIBB-Doku)
Text dt. und engl.
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; G 1.2.4.1.4 Verarbeitendes Gewerbe; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; Europäischer Qualifikationsrahmen; Chemische Industrie; Durchlässigkeit im Bildungssystem; Kompetenzprofil; Kompetenzniveau; Internationaler Vergleich